Back Cover: The Nanoparticle Size Effect in Graphene Cutting: A "Pac‐Man" Mechanism (Angew. Chem. Int. Ed. 34/2016). Issue 34 (20th June 2016) - Qiu, Zongyang; Song, Li; Zhao, Jin; Li, Zhenyu; Yang, Jinlong
Abstract : A "Pac‐Man" mechanism is revealed for the metal‐nanoparticle‐catalyzed cutting of graphene by employing a multiscale simulation approach. Z. Li et al. report in their Communication onpage 9918 ff. that although the overall cutting rate is proportional to the surface area of the nanoparticle, the rate‐limiting step of graphene cutting is actually at the graphene–metal interface. Such an apparent inconsistency turns out to be a result of the distinct etching behaviors at zigzag and armchair edge sites.